Evaluate the adequacy of disclosure as a solution to the problem of conflict of interest in medical research - Moklif, Alanazi Mansour; Ratoubi, Alanazi Mohammed (International Journal of Research in Medical Sciences, 2020)
A potential risk of conflict of interest currently exists in research. The financial considerations play a greater role in the decisions that are necessary in the process of research. Traditional pharmaceutical companies began to invest, not just in the commercial development of biomedical discoveries for the marketplace, but in the research centres that could deliver the discoveries. Cooperation and interdependence between industry and research institutions is not inherently wrong, but these unions must be regulated and managed through regulatory mechanisms. When a financial relationship is been disclosed, it would be closely evaluated in order to determine the risk of an undue influence leading to bias, or loss of scientific objectivity. To sum up, a conflict of interest is a potential, but not a certain occurrence. Banning funding for university research by industry is unrealistic. The only effective way to proceed is to implement oversight and regulation that makes both industry funding entities and researchers aware that their activities will be monitored for the benefit of public safety as the more valued concern.